Our experience of surgical treatment of patients with old total injury of rotator cuff tendon - V. V. Monastyrev; V. Yu. Vasilyev; M. E. Puseva; N. V. Tishkov (Acta Biomedica Scientifica, 2013)
Injury of rotator cuff tendon is a common cause of pain and dysfunction of shoulder joint. The aim. of this study was to evaluate clinical efficiency of surgical treatment of patients with old total rupture of rotator cuff tendon. 63 patients were operated in clinic of Scientific Center of Reconstructive and. Restorative Surgery SB RAMS during 2007—2012. Average age of the patients was 47,6 ±2,1 years. Patients were randomized into two groups of clinical comparison. Patients of the first group had open reinsertion of rotator cuff tendons with transosseous sutures. Patients of the second group had the same procedure with use of an additional metal construction. The observation period differed from 3 months to 5 years (26 ± 5,1 months in average). As the result of the research positive results were in 83,1 % and 82,4 % of cases respectively at the assessment with use of UCLA scale. Reinsertion of full rupture of rotator cuff tendons in spite of risk of trauma of operative treatment is an operation. of choice that gives maximum prospects to the restoration of patients' capability. But analyzed technical defects of known methods caused the creation of a new method of surgical treatment of old injuries of rotator cuff tendon and. the device for its realization.